"CONTROLLED VOCABULARY” AND ISSUES CONCERNING THE COMPILATION OF AN ENGLISH GEORGIAN LEARNER’S DICTIONARY - Khuskivadze, Elene (Online Journal of Humanities ETAGTSU, 2020)
The aim of the article is to represent the study that explores the necessity of the controlled vocabulary in a bilingual English-Georgian learner’s dictionary and the necessity of the reduction of polysemantic meanings of a word based on the frequency principle in an English –Georgian learner’s dictionary. It is necessary to combine the two main methodologies of lexicography: on the one hand, to get acquainted with the methodology of learner's lexicography and on the other hand to study the needs of the dictionary users. An experiment was planned and conducted with the participation of school students, which revealed interesting results. Thus, the study identified the need to create an English-Georgian learner’s dictionary tailored for students’ needs. <a title=""Controlled Vocabulary” and Issues Concerning the Compilation of an English Georgian Learner’s Dictionary" href="https://etag.tsu.ge/journal/files/05_Elene-Khuskivadze.pdf" target="_blank" rel="noopener">Full Text (PDF)